UI/UX Design Planning of Ququ Bakery Application Using the User Centered Design (UCD) Method - Anggraeni, Nabila Widya; Nugroho, Adi (Sistemasi: Jurnal Sistem Informasi, 2025)
This study aims to design the user interface (UI) and user experience (UX) of a birthday cake ordering application for Ququ Bakery in Semarang, Central Java, using the User-Centered Design (UCD) approach. The main issues faced by Ququ Bakery include limited promotional media, which currently relies solely on Instagram, as well as user difficulties in placing orders, checking prices, tracking order status, accessing promotions, and making payments. The objective of this research is to develop a web-based application UI/UX that addresses these challenges and enhances user satisfaction. The UCD method applied in this study consists of four stages: Understanding and Specifying the Context of Use, Specifying User Requirements, Designing Solutions to Meet User Requirements, and Evaluating Against Requirements. Evaluation was conducted using the System Usability Scale (SUS) through a questionnaire distributed to 96 respondents. The results indicate an SUS score of 90.35, categorized as “Excellent,” which demonstrates that the proposed application design achieves a very high level of usability and user satisfaction. These findings suggest that implementing the UCD approach effectively produces an intuitive, efficient, and user-oriented application design, which can significantly improve customer loyalty and engagement with Ququ Bakery.